Social competence following neonatal and childhood stroke. Issue 8 (19th December 2013) - Lo, Warren; Gordon, Anne; Hajek, Christine; Gomes, Alison; Greenham, Mardee; Perkins, Elizabeth; Zumberge, Nicholas; Anderson, Vicki; Yeates, Keith Owen; Mackay, Mark T.
Abstract : Background: Social functioning encompasses a range of important skills that an individual uses to interact with the social world. Previous studies suggest that social functioning (outcomes) may be impaired after childhood stroke, but research is limited. Aims: We examined the following: (1) the effect of ischemic stroke upon social outcomes in children; (2) the correlation of cognitive abilities and problem behaviors with social outcomes; and (3) the role of infarct characteristics as predictors of social outcomes. Methods: We conducted an observational case‐controlled study to compare children with neonatal or childhood onset stroke and controls with chronic asthma. Neurological deficits were measured with the Pediatric Stroke Outcome Measure. Cognitive abilities, problem behavior, adaptive behavior, and social outcomes were assessed with standardized measures. Results: Overall stroke cases were impaired in several areas of adaptive behaviors but not in cognitive ability, problem behaviors, or social outcomes. Children with more severe neurological deficits had impairments in a range of adaptive behaviors, social adjustment, and social participation. Impaired cognitive ability and more problem behaviors correlated with impaired social adjustment, particularly in stroke cases. Larger infarcts correlated with greater neurological impairment, lower IQ, and poorer social participation. Conclusions: Stroke can result in impaired adaptive and social functioning without apparent deficits in IQ or behavior. Infarct size, residual neurological deficits, impaired cognitive ability, and problem behaviors increase the risk for poor social adjustment and participation. These findings can help the clinician anticipate impaired social functioning after pediatric stroke, which is important because age‐specific treatments are available.